O06.3 Analysis of the treponema pallidum proteome for evidence of host protein mimicry; identification of a mechanism for bacterial persistence and establishment of latency during syphilis infection?. (8th July 2017) - Cameron, Caroline; Houston, Simon
Abstract : Introduction: The causative agent of syphilis, Treponema pallidum, is a highly invasive pathogen that can establish lifelong latency. Experimental evidence generated by our laboratory demonstrates a subset of T. pallidum proteins exhibits mimicry of host proteins, a strategy that may be used by T. pallidum to evade detection by the immune system and establishment of latency. Here we analysed all T. pallidum proteins of unknown function to assess the complete repertoire of potential host protein mimics expressed by this stealthy and highly successful pathogen. Methods: Amino acid sequences of 327 functionally unannotated protein-coding genes from T. pallidum ssp. pallidum (Nichols strain) were submitted to the protein fold recognition server, Phyre2. For each T. pallidum protein, the 20 top-ranked template matches and structural models were obtained. To identify potential T. pallidum host protein mimics, we analysed the source organism and functions of all high-confidence template proteins used for modelling (confidence scores/90%; alignment coverage/10%). Results: High-confidence structural predictions were generated for 51% of T. pallidum proteins with no assigned function (167/327). Analysis of these 167 functionally unannotated proteins identified a range of T. pallidum proteins predicted to adopt structural folds similar to domains from host proteins central to the processes of homeostasis and self-recognition, including Toll-like receptors, extracellular matrix components, and proteins involved in cell-signalling, complement and blood coagulation pathways. Conclusion: Our analyses have identified a complement of potential host protein mimics within T. pallidum . This novel finding will provide significant insight into T. pallidum virulence mechanisms for mediating host attachment and subverting host recognition, thereby aiding establishment of persistent infection. Our results also illustrate the power of molecular modelling for enhancing our understanding of microbial pathogenesis and disease establishment for bacterial pathogens with unique proteomes.